2014
DOI: 10.1002/2013jd021324
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ambient O2(a1Δg) on satellite-based laser remote sensing of O2columns using absorption lines in the 1.27 µm region

Abstract: Determination of CO 2 mixing ratio columns from space using Laser Absorption Spectroscopy (LAS) requires simultaneous measurements of CO 2 number density columns and knowledge of the dry atmospheric surface pressure. One approach to determining the surface pressure is to make an LAS column measurement of O 2 number density in the 7857.3-7921.7 cm À1 (1.27 μm) region of the O 2 ( 1 Δ) state. A complicating factor in the LAS O 2 measurement is the presence of a permanent but spatially variable natural source of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…A photochemical model taking O 2 (b, a, X) states and O( 1 D, 3 P ) states into account was developed by Mlynczak et al (1993) with the use of the basic daytime O 2 (a) kinetic model employed by Thomas (1990). The model of Mlynczak et al (1993) was extended by Sharp et al (2014) by including the three-body recombination reaction producing O 2 (a) during night time, see the R a1.1−2 reactions provided in Table 3. The model of Sharp et al (2014) also included processes related to the laser excitation, but these processes are not relevant for the present study and are excluded.…”
Section: The Modified Kinetic Model Of O 2 and O 3 Photolysis Productsmentioning
confidence: 99%
See 3 more Smart Citations
“…A photochemical model taking O 2 (b, a, X) states and O( 1 D, 3 P ) states into account was developed by Mlynczak et al (1993) with the use of the basic daytime O 2 (a) kinetic model employed by Thomas (1990). The model of Mlynczak et al (1993) was extended by Sharp et al (2014) by including the three-body recombination reaction producing O 2 (a) during night time, see the R a1.1−2 reactions provided in Table 3. The model of Sharp et al (2014) also included processes related to the laser excitation, but these processes are not relevant for the present study and are excluded.…”
Section: The Modified Kinetic Model Of O 2 and O 3 Photolysis Productsmentioning
confidence: 99%
“…The model of Mlynczak et al (1993) was extended by Sharp et al (2014) by including the three-body recombination reaction producing O 2 (a) during night time, see the R a1.1−2 reactions provided in Table 3. The model of Sharp et al (2014) also included processes related to the laser excitation, but these processes are not relevant for the present study and are excluded.…”
Section: The Modified Kinetic Model Of O 2 and O 3 Photolysis Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…The absorption and emission spectral features also interact with each other in atmospheric remote sensing. Sharp et al reported the impact of ambient O 2 (a 1 ∆ g ) on O 2 column remote sensing with satellite-based laser using absorption lines in the 1.27 µm band [11]. Bertaux et al evaluated the contribution of O 2 (a 1 ∆ g ) airglow to the retrieval accuracy of CO 2 mixing ratio columns in the MicroCarb optical concept [12].…”
Section: Introductionmentioning
confidence: 99%